PENGARUH PENGGUNAAN E-KOMIK INTERAKTIF TERHADAP HASIL BELAJAR DAN APRESIASI SENI TARI DAN MUSIK SISWA SEKOLAH DASAR - Fathul Fuadi, Muhammad; Titi Andaryani, Eka; Setiawan, Deni (STKIP Melawi, 2025)
This study aims to analyze the effect of interactive e-comics on elementary school students' learning outcomes and appreciation of dance and music. The study used a quasi-experimental method with a pretest-posttest control group design. The research subjects consisted of 70 fifth-grade students at SDIT Ibnu Yunsi Kota Binjai, divided into experimental and control groups. The instruments used were learning outcome tests and art appreciation questionnaires. The t-test results showed a significant difference (p < 0.05). Interactive e-comics were effective in improving students' learning outcomes and appreciation of the arts.